Caleta el Cobre 022 Martian meteorite: Increasing nakhlite diversity. (24th June 2020) - Krämer Ruggiu, L.; Gattacceca, J.; Devouard, B.; Udry, A.; Debaille, V.; Rochette, P.; Lorand, J.‐P.; Bonal, L.; Beck, P.; Sautter, V.; Busemann, H.; Meier, M. M. M.; et al.
Abstract: Caleta el Cobre (CeC) 022 is a Martian meteorite of the nakhlite group, showing an unbrecciated cumulate texture, composed mainly of clinopyroxene and olivine. Augite shows irregular core zoning, euhedral rims, and thin overgrowths enriched in Fe relative to the core. Low‐Ca pyroxene is found adjacent to olivine. Phenocrysts of Fe‐Ti oxides are titanomagnetite with exsolutions of ilmenite/ulvöspinel. Intercumulus material consists of both coarse plagioclase and fine‐grained mesostasis, comprising K‐feldspars, pyroxene, apatite, ilmenite, Fe‐Ti oxides, and silica. CeC 022 shows a high proportion of Martian aqueous alteration products (iddingsite) in olivine (45.1 vol% of olivine) and mesostasis. This meteorite is the youngest nakhlite with a distinct Sm/Nd crystallization age of 1.215 ± 0.067 Ga. Its ejection age of 11.8 ± 1.8 Ma is similar to other nakhlites. CeC 022 reveals contrasted cooling rates with similarities with faster cooled nakhlites, such as Northwest Africa (NWA) 817, NWA 5790, or Miller Range 03346 nakhlites: augite irregular cores, Fe‐rich overgrowths, fine‐grained K‐feldspars, quenched oxides, and high rare earth element content. CeC 022 also shares similarities with slower cooled nakhlites, including Nakhla and NWA 10153: pyroxene modal abundance, pyroxenes crystal size distribution, average pyroxene size, phenocryst mineral compositions, unzoned olivine, and abundant coarse plagioclase. Moreover, CeC 022 is the most magnetic nakhlite and represents an analog source lithology for the strong magnetization of the Martian crust. With its particular features, CeC 022 must originate from a previously unsampled sill or flow in the same volcanic system as the other nakhlites, increasing Martian sample diversity and our knowledge of nakhlites.